PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP MOTIVASI BELAJAR SISWA - Wulandari, Wulandari; Sakti, Hadi Gunawan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
Problem that occur at school in Indonesia language course, when teacher do teaching still use conventional methods such as speech, discussions, and group work,that is make students less motivated in learning and then when the teacher delivering the material still uses chalk and blackboard,because it does not heaving an LCD projector at school. In this causes student be less able to actively participate in the learning process of Indonesia language course. Purpose f this research was to determine effect of Jigsaw Learning Model towards Student Learning Motivation to Indonesian language course in 7th Grade Studen,AL-Ahyar Nw Islamic Junior high School State Bagik Polak, West Lombok, 2018/2019 Academic Year. Research methode use experimental methode and research design One Group Pre-tes Pos-tes Design. Research population using in7th Grade Student with 115 student,because number of population using more than 100 student so in this research using sample random sampling, withs sample of research use 28 studen totally. Data collection method used was the questionnaire method white documentation as acomplementary method. Analyz sinthe chi square formula(x2). The results of the study are x2 count of 19.551 and the value of x2 tables at a significant level of 5% with dk (fh-1)=2-1=1 greater than the value of x2 in the table (19,551>15,507) which means that HO is rejected and Ha is accepted it means: There is an Efect of Jigsaw Learning Model toword Student Learning Motivation to Indonesia language caerse in 7th Grade student AL-ahyar NW Islamic Junior High School State Bagek Polak West Lombok Regency 2018/2019 Academic Year.â€significantâ€